1984
DOI: 10.1182/blood.v64.1.131.bloodjournal641131
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the effect of influenza virus on polymorphonuclear leukocyte membrane responses

Abstract: Depressed chemotactic activity of polymorphonuclear leukocytes (PMNL) infected with influenza virus could be due to changes occurring at the plasma membrane. The present study examined the effect of unopsonized influenza virus on chemotaxis, adherence, receptor binding, shape change, membrane fluidity, and release of specific granules from PMNL. Chemotactic activity of PMNL under-agarose to the chemoattractants, zymosan-activated serum ( ZAS ) and N-formyl-methionyl-leucyl- phenylalanine (fMLP), and adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…We found that MIP-2 was also increased significantly in incubated BAL cells from co-infected lungs compared with either single-infected lungs or non-infected lungs, as reported previously [9]. These results also suggested the important roles of these cytokines/chemokines and neutrophils in the pathogenesis of severe pneumonia because of influenza virus and bacteria co-infection [27,28]. Braun et al reported elevated A1AT concentrations despite decreases of the NE and MPO concentrations in BALF from acute pneumonia patients, and suggested the importance of the balance between aggressive factors (NE, MPO, lysozyme and MIP-2) and protective factors (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…We found that MIP-2 was also increased significantly in incubated BAL cells from co-infected lungs compared with either single-infected lungs or non-infected lungs, as reported previously [9]. These results also suggested the important roles of these cytokines/chemokines and neutrophils in the pathogenesis of severe pneumonia because of influenza virus and bacteria co-infection [27,28]. Braun et al reported elevated A1AT concentrations despite decreases of the NE and MPO concentrations in BALF from acute pneumonia patients, and suggested the importance of the balance between aggressive factors (NE, MPO, lysozyme and MIP-2) and protective factors (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Reduced MPO activity in influenza virus infection was also observed in the whole lungs of mice with chronic P. aeruginosa infection. Influenza virus has been demonstrated to have direct effects on neutrophil functions in vitro, including inhibition of chemotaxis, oxidative function and lysosome-phagosome fusion [19,20]. Pang et al [16] reported that sputum neutrophils obtained from patients with bronchiectasis showed a significantly reduced capacity to secrete lysozyme, but not MPO by influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Whether granulocytes are productively infected or whether they have simply taken up infected cells or free virus remains to be determined. Polymorphonuclear leukocytes can harbor viruses (2,43,46,49), although it has rarely been shown that viruses infect these cells directly (reviewed in reference 1). On the other hand, it has been demonstrated that granulocytes take up virions; alternatively, infected cells or cell debris might be ingested by phagocytosing cells.…”
Section: Discussionmentioning
confidence: 99%